2022
DOI: 10.1101/2022.02.25.22271501
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Omicron variant on the response to SARS-CoV-2 mRNA Vaccination in multiple myeloma

Abstract: Multiple myeloma (MM) patients may have a reduced response to vaccination due to immunodeficiency. The humoral and cellular response to SARS-CoV-2 mRNA full vaccination and booster dose as well as the impact of spike variants, including the emerging Omicron one, are still unclear and have been investigated in this study in a cohort of MM patients and those with pre-malignant monoclonal gammopathies. Firstly, we have shown that MM patients with relapsed-refractory disease (MMR) had a reduced spike-specific anti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“… [68] A study in patients with monoclonal gammopathies at different stages of disease, including multiple myeloma (n = 40), showed that neutralizing antibody responses against Omicron (B.1.1.529) were reduced compared to the wild-type strain following the primary vaccine regimen, but were improved following a booster dose. [69] …”
Section: Immunocompromised Patientsmentioning
confidence: 99%
“… [68] A study in patients with monoclonal gammopathies at different stages of disease, including multiple myeloma (n = 40), showed that neutralizing antibody responses against Omicron (B.1.1.529) were reduced compared to the wild-type strain following the primary vaccine regimen, but were improved following a booster dose. [69] …”
Section: Immunocompromised Patientsmentioning
confidence: 99%